2019
DOI: 10.5505/deutfd.2019.86619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of locally applied Clinoptilolite (Froximun®) on seroma formation in a rat mastectomy and axillary lymph node dissection model

Abstract: Objective: Seroma formation is one of the most frequent complications following breast cancer surgery. Although many techniques and drugs have been investigated, no definitive data are available concerning how to prevent this complication. The present study aims to investigate impact of local clinoptilolite application on seroma formation in an experimental mastectomy model created in rats. Material and Method: Two groups with seven rats in each were randomised. Under general anesthesia, all rats underwent rig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“… 28 It has been reported that macrophages and fibroblasts gradually increase in number in the early stage of the healing process and reach their highest level and gradually decrease as the healing process progresses, and the antioxidant effect of clinoptilolite occurs at this early stage. 21 Garcia Godoy F. et al 29 reported that clinoptilolite added locally to the graft in the bone defect created in the mandible, similar to our results, provided positive effects on bone regeneration in the early period. In addition, they showed that there was no significant difference between the groups in terms of healing and bone formation in the late 30 and 60 days.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“… 28 It has been reported that macrophages and fibroblasts gradually increase in number in the early stage of the healing process and reach their highest level and gradually decrease as the healing process progresses, and the antioxidant effect of clinoptilolite occurs at this early stage. 21 Garcia Godoy F. et al 29 reported that clinoptilolite added locally to the graft in the bone defect created in the mandible, similar to our results, provided positive effects on bone regeneration in the early period. In addition, they showed that there was no significant difference between the groups in terms of healing and bone formation in the late 30 and 60 days.…”
Section: Discussionsupporting
confidence: 88%
“…Aksoy S.O. et al 21 applied Froximun Toxaprevent Skin powder® in powder form according to the wound size after mastectomy and axillary dissection in rats, and closed the wound area with sutures after local application. Uraloğlu M. et al 22 applied Froximun Toxaprevent Skin powder® to the wounds opened on the back skin of the rats locally, in powder form and according to the wound size, and did not suture the wounds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The majority of these studies; it is designed on the basis of reducing the surgical cavity area, shortening the inflammatory process, and accelerating healing. In this context, different surgical techniques, pressure dressings, techniques that provide immobilization, tissue adhesives, and different agents have been involved in studies to prevent this complication (19,20). Platelets have an important role in hemostasis, tissue regeneration, and host defense.…”
Section: Discussionmentioning
confidence: 99%